The king and the cemeteries : toward a new understanding of Josiah's reform - Barrick, W. Boyd, 1946- (Supplements to Vetus Testamentum,, 2002)
This book presents new examinations of the reports of Josiah's reform in 2 Kgs. 23:4-20 + 24 and 2 Chron. 34:3-7 and related biblical passages (especially 1 Kgs.12:33-13:32), concentrating on the likely compositional history of this material and its usefulness as a source for reconstructing the likely history of Josiah's reign. Chapter 1 introduces the inquiry, reviewing the state of the question and methodological caveats. Chapters 2-6 are devoted to issues of composition and redaction, Chapters 7-10 to issues of historical context and circumstance. Both literary and archaeological materials are considered. These studies contribute fresh analyses and new propositions to the scholarly discussion of this seminal moment in the history of biblical Israel.